A revised phytosociological nomenclature for the Italian 'Quercus cerris' woods - Terzi, Massimo; Ciaschetti, Giampiero; Fortini, Paola; Rosati, Leonardo; Viciani, Daniele; Di Pietro, Romeo (Mediterranean Botany, 2020)
This paper aims to revise the phytosociological nomenclature of the Quercus cerris woods occurring in Italy with particular attention to associations, subassociations, and suballiances. The syntaxa included in this revision were selected based on a physiognomical criterion, i.e., woods with dominance or codominance of Quercus cerris. The nomenclatural revision complied with the International Code of Phytosociological Nomenclature. Correct names and Authors’ citations were considered for all the syntaxa analyzed (121), and, in most cases, other information about nomenclatural types, localities, synonyms, classification, and other notes was reported. As regards the alliance level, the correct application of the name Melittio albidae-Quercion frainetto ―whose original diagnosis and type-association occur in Italy― was discussed. In all, 31 syntaxon names were validated or described: two suballiances (Campanulo medii-Ostryenion carpinifoliae and Pulmonario apenninae-Carpinenion betuli), nine associations and 20 subassociations. Five lectotypes were also designated.